Fluid-Structure-Sound Interactions and Control Proceedings of the 3rd Symposium on Fluid-Structure-Sound Interactions and Control - Zhou, Yu.; Lucey, A.D.; Liu, Yang.; Huang, Lixi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
These proceedings primarily focus on advances in the theory, experiments, and numerical simulations of turbulence in the contexts of flow-induced vibration and noise, as well as their control. Fluid-related structural vibration and noise problems are often encountered in many engineering fields, increasingly making them a cause for concern. The FSSIC conference, held on 5-9 July 2015 in Perth, featured prominent keynote speakers such as John Kim, Nigel Peake, Song Fu and Colin Hansen, as well as talks on a broad range of topics: turbulence, fluid-structure interaction, fluid-related noise and the control/management aspects of these research areas, many of which are clearly interdisciplinary in nature. It provided a forum for academics, scientists and engineers working in all branches of Fluid-Structure-Sound Interactions and Control (FSSIC) to exchange and share the latest developments, ideas and advances, bringing them together researchers from East and West to push forward the frontiers of FSSIC, ensuring that the proceedings will be of interest to a broad engineering community.
Aeroacoustics and Applications -- Sound and its Interaction with Structure -- Hydroacoustics and Bubbles -- Boundary Layer and Skin Friction Drag Reduction -- Bluff Body Wakes -- Jets -- Other Flows -- Flexible surfaces in axial flow -- Flow-Induced Vibrations -- Vortex Shedding.
Keywords: Fluid mechanics; Acoustics; Continuum mechanics; Multibody systems; Vibration; Mechanics, Applied; Engineering Fluid Dynamics; Acoustics; Continuum Mechanics; Multibody Systems and Mechanical Vibrations